1984
DOI: 10.1177/019459988409200602
|View full text |Cite
|
Sign up to set email alerts
|

Nonhypersomnolent Patients with Obstructive Sleep Apnea

Abstract: Until recently, snoring had been considered both a medical enigma and a psychosocial problem. Snoring is now considered to be an acoustic phenomenon produced by vibration of the soft palate and the tonsillar pillars. We describe 20 patients with a clinical complaint of excessive snoring who were referred to rule out obstructive sleep apnea. All patients were without symptoms of daytime sleepiness and failure of the right heart. Twenty subjects were studied, 18 of whom were males. All subjects were monitored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…It is necessary to take a careful history from the patient and partner as this can lead to helpful information regarding snoring, apnoeic events and duration, nightime wakening, morning headaches and daytime somnolence. The absence of somnolence does not mean the absence of sleep apnoea (Moran et al, 1984). The patients' partners in our series reported breath holding episodes occurring in 93 per cent and also suggested that 48 per cent had episodes lasting 10 s or more.…”
Section: Discussionsupporting
confidence: 44%
“…It is necessary to take a careful history from the patient and partner as this can lead to helpful information regarding snoring, apnoeic events and duration, nightime wakening, morning headaches and daytime somnolence. The absence of somnolence does not mean the absence of sleep apnoea (Moran et al, 1984). The patients' partners in our series reported breath holding episodes occurring in 93 per cent and also suggested that 48 per cent had episodes lasting 10 s or more.…”
Section: Discussionsupporting
confidence: 44%
“…Some studies suggest SDB may be involved in this complaint, 17–19 but others do not 1,2,40 . Finally, snoring undoubtedly relates to SDB, 41–44 but although SDB is usually accompanied by some form of snoring, snoring may also occur without any disturbance in ventilation. In this report, we employ this three‐way classification of symptomatic status (hypersomnia, insomnia, parasomnia) as an additional risk factor.…”
mentioning
confidence: 99%
“…In a study of heavily snoring but otherwise asymptomatic men, the incidence of upper airway obstruction (apnea-hypopnea index [ A H ] of greater than 5) was 13% (Berry, Webb, Block, & Switzer, 1986). In fact, in our laboratory, we have documented the presence of AHIs of greater than 20 in a similar population (Moran, Orr, Fixley, & Wittels, 1984). Given that the natural precursors to clinically significant OSA exist in appreciable numbers in the general population, especially among males, what are the factors that ultimately lead to the development of clinically significant OSA?…”
Section: Natural Historymentioning
confidence: 62%